Detection of monoamine oxidase a in brain of living rats with [18F]fluoroethyl‐harmol PET. Issue 1 (24th September 2014) - Cumming, Paul; Skaper, Dirk; Kuwert, Torsten; Maschauer, Simone; Prante, Olaf
<x xml:space="preserve">Abstract</x> The efficient radiosynthesis for the MAO‐A ligand [18F]fluoroethyl‐harmol is reported. Initial PET examinations reveal the ligand to be retained throughout rat brain during 90 min, whereas pretreatment with pargyline results in substantially increased washout, from which binding potentials in the range of 1.4–2.1 can be calculated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>